Cronobacter spp. in Commercial Powdered Infant Formula Collected From Nine Provinces in China: Prevalence, Genotype, Biofilm Formation, and Antibiotic Susceptibility - Fei, Peng; Jing, He; Ma, Yan; Dong, Gege; Chang, Yunhe; Meng, Zhaoxu; Jiang, Shilong; Xie, Qinggang; Li, Shuzhen; Chen, Xi; Yang, Weiwei (Frontiers in Microbiology, 2022)
The purpose of this study was to investigate the prevalence of Cronobacter spp. in commercial powdered infant formula (PIF) from nine provinces in China from March 2018 to September 2020, and to reveal the genotype, biofilm-forming ability, and antibiotic susceptibility of these isolates. A total of 27 Cronobacter strains, consisting of 22 Cronobacter sakazakii strains, 3 Cronobacter malonaticus strains, 1 Cronobacter turicensis strain, and 1 Cronobacter dublinensis strain, were isolated from 3,600 commercial PIF samples with a prevalence rate of 0.75%. Compared with the other 8 provinces, PIF from Shaanxi province had a higher prevalence rate (1.25%) of Cronobacter spp. These isolates were divided into 14 sequence types (STs), and 6 Cronobacter serotypes. The main Cronobacter STs were ST4, ST1, and ST64, and the dominant Cronobacter serotype was C. sakazakii serotype O2. Approximately 88.89% of Cronobacter isolates had a strong ability (OD595 > 1) to form biofilms on tinplate, among which the strains with ST4 were more dominant. All isolates were susceptible to ampicillin-sulbactam, ceftriaxone, cefotaxime, sulfadiazine, sulfadoxine, trimethoprim-sulfamethoxazole, gentamicin, tetracycline, ciprofloxacin, and colistin, while 55.56 and 96.30% isolates were resistant to cephalothin and vancomycin, respectively. Taken together, our findings highlighted the contamination status and characterization of Cronobacter spp. in commercial PIF from nine provinces of China, and provided guidance for the effective prevention and control of this pathogen in the production of PIF.